Using surveillance data to evaluate the effectiveness of inactivated/mRNA COVID-19 vaccine boosters in preventing fatal outcomes among severe COVID-19 cases during the current ambit of SARS-CoV-2 XBB and JN.1 variant circulation - Lo, Eugene S. K.; Wong, Lok Tung; So, Serana C. Y.; Mohammad, Kirran N.; Law, Ka Yi; Chan, Kam Suen; Chan, Chung Lam; Lo, Dawin; Kung, Kin Hang; Chuang, Shuk Kwan (Frontiers in Public Health, 2025)
BackgroundDespite the rapid evolution of the SARS-CoV-2 viruses, vaccines targeting ancestral strains remain widely used. This study evaluates the effectiveness of ancestral strains inactivated and mRNA COVID-19 vaccine boosters in preventing fatal outcomes among severe COVID-19 cases during the circulation of the XBB and JN.1 variants.MethodsWe analyzed 2,157 severe COVID-19 cases (aged ≥50) reported to the Centre for Health Protection from the hospital authority-managed public hospitals between January 30, 2023, and January 29, 2024. Logistic regression was used to investigate the relationship between vaccination status and fatal outcomes, adjusting for age, sex, and residential status in residential care homes for the older adult (RCHE), and other demographic factors.ResultsAmong the 2,157 cases, 764 (35.4%) succumbed within a 28-day follow-up. Fatal outcomes were more common among older individuals, RCHE residents, and those unvaccinated or with incomplete initial vaccination (zero to two doses). Fewer deaths had received ancestral strains mRNA or inactivated booster doses compared to those not receiving booster. Univariate logistic regression revealed the lowest in-hospital mortality odds ratio for mRNA booster recipients, followed by inactivated booster recipients, and then those with completed initial vaccination (three doses). After adjusting for confounders, booster vaccination remained significantly associated with reduced in-hospital mortality.ConclusionVaccines based on ancestral strains maintain some degree of effectiveness against recently emerged variants, offering insights for healthcare policies in regions where earlier generations of inactivated and mRNA vaccines continue to be administered.